2002
DOI: 10.1093/rheumatology/41.11.1249
|View full text |Cite
|
Sign up to set email alerts
|

Synovial fluid from patients with rheumatoid arthritis inhibits neutrophil apoptosis: role of adenosine and proinflammatory cytokines

Abstract: The microenvironment of rheumatoid SF is a proinflammatory milieu responsible for the in loco persistence of activated and long-surviving neutrophils. Adenosine plays a crucial role in this phenomenon, which is related to anti-apoptotic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
99
0
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(107 citation statements)
references
References 58 publications
3
99
0
5
Order By: Relevance
“…For instance, in rheumatoid arthritis (RA), the most common form of autoimmune joint inflammation, neutrophils are represented preponderantly in the diseased joint fluid and display a prolonged lifespan and reduced migratory activity, suggesting the accumulation of factor(s) in RA that promote neutrophil plasticity (23)(24)(25).…”
mentioning
confidence: 99%
“…For instance, in rheumatoid arthritis (RA), the most common form of autoimmune joint inflammation, neutrophils are represented preponderantly in the diseased joint fluid and display a prolonged lifespan and reduced migratory activity, suggesting the accumulation of factor(s) in RA that promote neutrophil plasticity (23)(24)(25).…”
mentioning
confidence: 99%
“…There is evidence of B-cell anergy for soluble antigens at serum concentration of >0.1 nM (34). Even in inflammatory conditions like rheumatoid arthritis, GM-CSF is present in synovial fluid at <35 pM (31,35). One group has reported that the frequency of autoantibodies in normal subjects reaches 100% if cytokine-autoantibody complexes are dissociated at low pH before autoantibodies are measured against IL-2, granulocyte colony-stimulating factor (G-CSF), VEGF, TNF, IL-8 (32), and GM-CSF (33).…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12] Indeed, a percentage of neutrophils obtained from lungs in inflammatory lung injury and from synovial fluids of patients with rheumatoid arthritis have been seen to persist for days. [13][14][15][16] The dogma that neutrophils are all alike is countered by a growing number of studies showing the functional heterogeneity of neutrophils. Neutrophil subsets have been demarcated with identifiable characteristics in terms, for example, of their expression of formyl-methionyl-leucylphenylalanine (fMLP) receptors.…”
mentioning
confidence: 99%